Prediction of thermodynamic properties from pure compound information: Characterization of fullerenes - Peukert, Wolfgang; Schürer, Gudrun (Applied Surface Science, 2005)
Fullerenes are widely studied not only in material, but also in life science due to their special properties. Their surface properties determine their interaction with the environment and influence adsorption as well as biodistribution. In this work, the surfaces of a series of fullerenes and polyhydroxylated C-fullerenes were investigated using density functional theory (DFT)/conductor-like screening model (COSMO)-calculations. The dependence of the screening charge density from the curvature of a carbon hexagon and its effect on the adsorption behavior was studied. The estimation of thermodynamic properties of multiply functionalized C-molecules gives promising qualitative results using only properties of the pure compounds. © 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; DFT; Fullerenes; Functionalization